Acupuncture Therapy for Side Effect Management in Head and Neck Cancer Radiotherapy: A Case Report - Natalia, Zellah Fransisca; Mihardja, Hasan (http://dharmais.co.id/, 2026)
Introduction: In addition to reducing tumor size, radiotherapy in head and neck cancer patients can lead to several negative effects, such as dysphagia, xerostomia, and mucosal infections. The prevalence of dysphagia due to head-neck radiation reaches 60% to 75%. If this condition is not treated properly, it will cause malnutrition, reduce the quality of life, and increase mortality rates. Therapy for post-radiation side effects of the head and neck generally uses medications. However, the price is quite high and may cause additional side effects. This case report aims to provide another alternative to treat post-radiation side effects without additional side effects and to prevent complications due to the side effects of head and neck radiationCase Presentation: A 54-year-old male patient had complaints of hypersalivation and dysphagia after radiotherapy due to sinonasal squamous cell carcinoma. This complaint was accompanied by the presence of blisters and hard yellowish plaques in the patient's mouth. The patient came to the acupuncture clinic with a pain score of 5, as measured by the Numeric Rating Scale (NRS), drooling severity and frequency scale (DSFS) was 4, and quality of life score of 2 and 53.08 by the MD Anderson Dysphagia Inventory (MDADI). He received manual acupuncture therapy on the face, ears, neck, hands, and feet with a frequency of twice per week and a duration of 30 minutes per session, for a total of 12 sessions. After complete acupuncture therapy, the pain decreased from NRS 5 to NRS 0, DSFS 4 to DSFS 1, and quality of life from MDADI 2 and 53.08 to MDADI 5 and 72.68. These results lasted until the end of follow-up at week 4 without side effects.Conclusions: Acupuncture can reduce complaints of post-radiotherapy head and neck side effects, especially dysphagia and hypersalivation. Also, improve the quality of life of cancer patients.